ANALISIS KEAKTIFAN BELAJAR SISWA MENGUNAKAN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT PADA MATA PELAJARAN BAHASA INDONESIA DI KELAS IV SD SWASTA PAB 5 KLUMPANG - Tri Kartika Handayani; Sutarini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to determine how student learning activity is influenced by the use of the Teams Games Tournament (TGT) learning model in the Indonesian language subject in grade IV at SD Swasta PAB 5 Klumpang, and to identify the challenges faced by teachers in implementing the TGT model in the Indonesian language learning process in grade IV at the same school. This research uses a qualitative research method with a descriptive approach. The participants in this study are the sources of information or data required for the research, namely the teacher and the grade IV students of SD Swasta PAB 5 Klumpang. The results of the research conducted in grade IV at SD Swasta PAB 5 Klumpang indicate that student learning activity improves during the learning process when using the Teams Games Tournament model. This is evidenced by the students’ enjoyment, attention to the learning process, interest, and active participation in the learning process. The enthusiasm and motivation of students can be observed throughout the lesson. The challenges faced by the teacher are not too significant, such as students feeling that the group division made by the teacher is unfair. However, the teacher successfully addresses these challenges